S-Doped Graphene Oxide/N-Doped Graphene Oxide/PANI: A Triple Composite for High-Performance Supercapacitor Applications - Yasa, Sezgin; Kumbasi, Okyay; Arvas, Melih Besir; Gencten, Metin; Sahin, Mutlu; Sahin, Yucel (ELECTROCHEMICAL SOC INC, 2023)
In this study, nitrogen doped graphene oxide(N-GO) and sulfur doped graphene oxide(S-GO) were produced in one step, and two of these prepared materials were converted into composite form with polyaniline(PANI). For the first time in the literature, triple composite electrode materials with two heteroatom doped graphene oxides and PANI were prepared for supercapacitors. In this context, heteroatom doped graphene oxides and PANI were characterized using spectroscopic and microscopic methods. With the ternary composites formed, anode and cathode electrode materials for coin cell type supercapacitors in asymmetrical form were characterized by electrochemical methods. The capacitive behavior of the prepared supercapacitors was investigated by cyclic voltammetry(CV) and electrochemical impedance spectroscopy(EIS) method. The change of capacitive behavior according to the number of cycles was determined by cyclic charge-discharge tests. With the electrode materials obtained with heteroatom doped graphene oxides/PANI composites, it reached the highest areal capacitance value of 79.7 mF.cm(-2) at 10 mV.s(-1) scan rate. The coin cell type asymmetric supercapacitors retained more than 100% of their initial specific capacitance at the end of the 1500 cycle.
Keywords: SOLID-STATE SUPERCAPACITORS; ENERGY-STORAGE; POLYANILINE; ELECTRODE; HYBRID; REDUCTION; OXIDATION; Materials Science; Physics